The Supportive Role of International Government Funds on the Progress of Sepsis Research During the Past Decade (2010-2019): A Narrative Review - Yuxin Leng PhD; Chengjin Gao MD; Fang Li PhD; Enzhong Li PhD; Fengzhu Zhang MSc (SAGE Publishing, 2022)
This narrative review aimed to clarify the characteristics of international government support for sepsis research, trends in published literature on sepsis, and potential contributions of government-source grants to progress in sepsis research between fiscal years 2010 and 2019. The data in this study were collected from the National Institutes of Health (NIH, https://projectreporter.nih.gov/reporter.cfm/ ) of the United States of America (USA), National Natural Science Foundation of China (NSFC, https://isisn.nsfc.gov.cn/egrantweb/ ), and Japan Society for the Promotion of Science (JSPS, https://kaken.nii.ac.jp/ ). All sepsis-related projects approved by the NIH, NSFC, and JSPS were retrieved by searching the project titles, abstracts, and key words for "sepsis," "septic shock," or "sepsis inflammatory response syndrome" between 2010 and 2019. Representative sepsis-related studies published between Jan 2010 and Aug 2020 by the first/corresponding authors from these countries were obtained by searching the PubMed database using Medical Subject Heading terms for "sepsis" in representative journals, including Nature , Cell, Science, The Lancet, New England Journal of medicine (New Engl J Med), The Journal of American Medical Association (JAMA), Critical Care Medicine (CCM), Intensive Care Medicine (ICM), Chest, Annals of Emergency Medicine (Ann Emerg Med), and American Thoracic Society journals (ATS). The total/annual institutional budgets, major funding mechanisms and schemes, superior institutions and individual principal investigators, and published original research articles in the field of sepsis in the USA, China, and Japan during the past decade were investigated. The national supporting schemes of the NIH, NSFC, and JSPS were similar. Support from these institutions is quite important for the development of the field of "sepsis" which was acknowledged in 57-64% of original research articles published in CCM. For the future development of precision medicine in sepsis, more government funding support is necessary.